The political role of the business firm: An ordonomic concept of corporate citizenship developed in comparison with the Aristoleian idea of individual citizenship - Ingo Pies; Markus Beckmann; Stefan Hielscher (Martin-Luther-Universität Halle-Wittenberg, Lehrstuhl für Wirtschaftsethik, 2012)
This is an essay in conceptual clarification: by way of comparison with the Aristotelian idea of individual citizenship for the antique polis, this article develops an ordonomic concept of “corporate citizenship” that offers two insights for academic scholarship. First, we clarify what is meant by a company's political role. Companies take such a role if they do not confine themselves to acting as bourgeois within the basic business game of producing goods and services, but also participate as citoyen in the meta games of political rule-setting processes and rule-finding discourses. Second, we show that the political dimension of corporate citizenship need not weaken or compromise a company's role as an economic actor. Rather, in light of deficient institutional rules, companies need to take a political role if they wish to pursue their self-perfection as economic agents for value creation. This means that in processes of new governance the economic and political roles of the firm need not contradict each other but can follow the same win-win logic of individual self-perfection through cooperative social interactions. – – Dieser Aufsatz dient zur konzeptionellen Klärung des Begriffs von ,,Corporate Citizenship“: Anhand eines Vergleichs mit der aristotelischen Idee individueller Bürgerschaft in der antiken Polis entwickelt dieser Artikel ein ordonomisches Konzept von ,,corporate citizenship“, das für die aktuelle Debatte über die Bürgerschaft korporativer Akteure in der Globalisierung zwei Einsichten formuliert. Erstens klärt der Beitrag, was es heißt, dass Unternehmen eine politische Rolle einnehmen. Unternehmen nehmen diese politische Rolle wahr, wenn sie sich nicht nur als Bourgeois im Basis-Spiel der Produktion von Gütern und Dienstleistungen betätigen, sondern auch als Citoyen an den Meta-Spielen der politischen Regelsetzungsprozesse und Regelfindungsdiskurse mitwirken. Zweitens zeigt der Beitrag, dass eine solche politische Dimension von Corporate Citizenship keineswegs zu einer Schwächung oder Außerkraftsetzung der wirtschaftlichen Rolle von Unternehmen führen muss. Vielmehr wird angesichts einer fehlerhaften Rahmenordnung die Übernahme einer politischen Rolle für Unternehmen notwendig, wenn sie ihre Selbstvervollkommnung als ökonomische Wertschöpfungsagenten zum Ziel haben. In funktionalen New-Governance-Prozessen müssen sich die politische und wirtschaftliche Rolle von Unternehmen daher nicht widersprechen, sondern können prinzipiell der gleichen Win-win-Logik individueller Selbstvervollkommnung durch wechselseitige vorteilhafte Interaktionen folgen.
urn:nbn:de:gbv:3:2-17513
Keywords: 330; Aristotle; corporate citizenship; ordonomics; self-perfection; value creation; Aristoteles; Corporate Citizenship; Ordonomik; Selbstvervollkommnung; Wertschöpfung